Complete Genome Sequences of Four Natural Pseudomonas Isolates That Catabolize a Wide Range of Aromatic Compounds Relevant to Lignin Valorization - Hatmaker, E. Anne (Microbiol Resour Announc, 2020)
Many soil microorganisms have evolved catabolic strategies to utilize phenolic compounds arising from depolymerized lignin. We report the complete genome sequences of four Pseudomonas sp. isolates that demonstrated robust growth on a wide range of aromatic monomers and dimers that are relevant to the valorization of lignin into value-added chemicals.